Compliance with hand hygiene: reference data from the national hand hygiene campaign in Germany. Issue 4 (April 2016) - Wetzker, W.; Bunte-Schönberger, K.; Walter, J.; Pilarski, G.; Gastmeier, P.; Reichardt, Ch.
Summary: Hand hygiene is a key measure to prevent healthcare-associated infection. To promote hand hygiene nationally the German campaign 'Aktion Saubere Hände' was launched in January 2008, based on the World Health Organization's 'Clean Care is Safer Care' initiative. We report the first results from a full year of data collection on hand hygiene compliance recorded with the help of a renewed observation tool. Data were based on submissions from 109 participating hospitals collected from 576 wards between January 1st and December 31st, 2014. The overall median compliance was 73%, ranging from 55% (10th percentile) to 89% (90th percentile). The results demonstrated only small differences between adult and non-adult intensive care units (ICUs) with neonatal ICUs and paediatric non-ICUs maintaining higher compliance than adult care units. Performance among nurses was better than physicians, and overall rates of hand hygiene performance were significantly higher after patient contact than before.